Identificação de hidrocarbonetos policíclicos aromáticos em cachaça mantida em embalagens de poli(tereftalato) de etileno, sob diferentes condições de armazenamento - Abrantes, Ana Paula (2022)
Cachaça is an beverage exclusively from Brazil, with peculiar sensory characteristics and great historical, cultural and economic scope. It has been conquering the national and international market, standing out for being the second most consumed beverage in the domestic market and the third most consumed. distillate in the world. All stages of production of this distillate influence the volatile components of the product, forming the main compounds, ethanol and water, and the secondary compounds, which are responsible for the sensory characteristics of the beverage. Other substances, considered to be negative during the production chain, can be produced. Contaminants such as polycyclic aromatic hydrocarbons (PAH's), commonly found in beverages and foods, have been studied because they have carcinogenic and genotoxic characteristics. One of the sources of contamination of cachaça is the use of inappropriate containers for the storage of this distillate, as well as the packaging conditions. Packaging such as poly(ethylene terephthalate) (PET) has been widely used as containers for beverages because they have convenient characteristics, are mechanically resistant to impact, are colorless and inert compared to other plastics. However, it is essential that care be exercized in the use of polymeric packaging with regard to the packaging-product interaction and the migration factor of compounds potentially harmful to human health, such as HPA's. The objective of this work was to analyze the physicochemical and chromatographic qualities of a sample of cachaça packed in PET containers under different storage conditions (laboratory, refrigerator, under continuous incidence of solar radiation and protected from light). The identification and quantiffication of HPA's in the same beverage was also determined after a period of 12 months. The physical-chemical analyses were performed according to the method established by the Ministry of Agriculture, Livestock and Supply (MAPA) and the analyses of the HPA's were performed by high performance liquid chromatography. In the characterization of PET, thermal analyses of the polymers were performed using differential scanning calorimetry (DSC), thermogravimetry (TGA) and Fourier transform infrared (FTIR). The quality of the samples was affected by the PET packaging and storage conditions caused by losses of the water-ethanol fraction, oxidation reaction and polymer degradation processes. The cachaça samples stored in PET containers under laboratory conditions contained higher concentrations of the compounds benzo[a]pyrene (BaP) and benzo[a]anthracene than that of the sample stored in a glass container, and the BaP concentration is the sample subjected to solar radiation exceeded the maximum limit allowed by the European Union. These HPA’s are considered cancer markers. It is inferred, therefore, that PET, despite having characteristics suitable for use in the cachaça packaging industry, can interfere with the quality of the distillate under certain storage conditions, and it is not ideal for storing this beverage.